FOREIGN DIRECT INVESTMENT FLOWS IN THE PERIOD OF WORLD ECONOMIC CRISIS - Rafal Warzala (European Scientific Journal, ESJ, 2013)
The core of this article is to study the impact of the last world financial crisis on the same period world foreign direct investment fluctuations. As last World Investment Report (WIR 2012) appear the current world financial crisis involved in the foreign direct investment flows drop. That was characteristic for the EU economy, too. The main reasons of that are the descending investment capability of corporations, because of poorer profits level and higher costs of bank credits. The important argument for corporation investment slump, is that the perspective of world economic growth are unfavourable.